Umbilical cord-derived mesenchymal stem cell extracts reduce colitis in mice by re-polarizing intestinal macrophages - Ji-young Song (Nature Portfolio, 2017)
Abstract Human umbilical cord mesenchymal stem cells (hUC-MSCs), originating in Wharton’s jelly, are multipotent stem cells that home to damaged tissues and can modulate the immune system. We examined whether administering extracts of MSCs (MSC-Ex) instead of MSCs could augment the beneficial effects of MSC therapy by overcoming the low homing efficiency of MSCs systemically administered in inflammatory bowel diseases (IBD). Dextran sodium sulfate-induced colitis model was established in C57BL/6 mice, and MSC-Ex was administered intraperitoneally. MSC-Ex reduced colitis, disease activity index (DAI), and histological colitis scores, and increased the body weight. Treatment with MSC-Ex completely blocked the induction of inflammatory cytokines, which were strongly detected in mice with colitis. MSC-Ex shifted the macrophage functional phenotype from M1 to M2 by decreasing the levels of MCP1, CXCL9, and iNOS, but increasing the levels of IL-10, LIGHT, CCL1, and Arg-1. MSC-Ex recovered the destruction of the epithelial barrier in the differentiated Caco-2 cells in vitro. Treatment with MSC-Ex was more potent than that with MSC in reducing DAI, the histological score, and nitrite levels. These data strongly support that MSC-Ex treatment can be a potent approach to overcome severe refractory IBD.